2004
DOI: 10.1128/mcb.24.21.9305-9316.2004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Steps of Mammalian Homologous Repair with Distinct Mutagenic Consequences

Abstract: Repair of chromosomal breaks is essential for cellular viability, but misrepair generates mutations and gross chromosomal rearrangements. We investigated the interrelationship between two homologous-repair pathways, i.e., mutagenic single-strand annealing (SSA) and precise homology-directed repair (HDR). For this, we analyzed the efficiency of repair in mammalian cells in which double-strand break (DSB) repair components were disrupted. We observed an inverse relationship between HDR and SSA when RAD51 or BRCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

48
560
5
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 450 publications
(614 citation statements)
references
References 60 publications
48
560
5
1
Order By: Relevance
“…To verify that this method specifically measures SSA, we compared the effect of the knockdown of RAD52 (which is critical for SSA) and of BRCA2 (which is critical for HR). 23 We observed that BRCA2 knockdown specifically impaired HR, whereas RAD52 knockdown specifically impaired SSA (Fig. 3A).…”
Section: Discussionmentioning
confidence: 79%
“…To verify that this method specifically measures SSA, we compared the effect of the knockdown of RAD52 (which is critical for SSA) and of BRCA2 (which is critical for HR). 23 We observed that BRCA2 knockdown specifically impaired HR, whereas RAD52 knockdown specifically impaired SSA (Fig. 3A).…”
Section: Discussionmentioning
confidence: 79%
“…Either BRCA1 or BRCA2 mutation reduces the efficiency of HR induced by a site-specific DSB [83][84][85][86][87]. Errorprone repair of the DSB by single strand annealing (SSA) is increased in BRCA2 mutants [87,88]-a pattern reminiscent of HR mutants in yeast and in other vertebrate cells. In contrast, SSA is partly dependent on BRCA1, suggesting that BRCA1 also participates in an earlier step in HR, perhaps working with the MRN complex to control processing of the DSB end [88,89].…”
Section: Role Of Brca1 and Brca2 In Hr Regulationmentioning
confidence: 99%
“…Errorprone repair of the DSB by single strand annealing (SSA) is increased in BRCA2 mutants [87,88]-a pattern reminiscent of HR mutants in yeast and in other vertebrate cells. In contrast, SSA is partly dependent on BRCA1, suggesting that BRCA1 also participates in an earlier step in HR, perhaps working with the MRN complex to control processing of the DSB end [88,89]. These studies do not assay HR at stalled forks, since the induced DSB has no relation to replication arrest.…”
Section: Role Of Brca1 and Brca2 In Hr Regulationmentioning
confidence: 99%
“…Most studies investigating the NBS1 Glu185Gln polymorphism have focused on assessing the risk of breast cancer [32]. There is only one publication on this NBS1 polymorphism and risk of colorectal cancer [33]. The XRCC3 protein interacts with Rad51-related proteins in the process of homologous recombination.…”
Section: Introductionmentioning
confidence: 99%